Identifying Symbolic Violence in the Comic Version of “Cinderella” - Linda, Juliana (Lingua Susastra, 2024)
This study aims to identify and analyze instances of symbolic violence, a concept introduced by Pierre Bourdieu, in the comic adaptation of the short story "Cinderella." Symbolic violence refers to the subtle, often invisible forms of domination and oppression embedded in social structures and practices. By employing a descriptive qualitative method and applying Bourdieu's theory, this research seeks to illuminate how power imbalances and social hierarchies are perpetuated through seemingly innocuous interactions and cultural norms. The findings reveal that Cinderella experiences various forms of symbolic violence, including acts of domination, excessive demands, favoritism, mockery, emotional manipulation, and the suppression of truth. These instances serve to maintain the status quo and reinforce power dynamics between Cinderella and her oppressors. By exposing these subtle yet pervasive forms of violence, this study contributes to the broader understanding of how symbolic violence operates in literature and society. The insights gained can inform future research on the representation of power dynamics in popular culture and the ways in which symbolic violence shapes social interactions and individual experiences. Ultimately, this study underscores the importance of recognizing and challenging the hidden forms of oppression that often go unnoticed in daily life.